Cryosurgical method for nervus vagus ablation in experimental studies - Chyzh, Mykola; Belozorov , Igor; Aschabov , Dmytro; Komyshanchenko , Dmytro; Globa , Vyacheslav; Marchenko , Larysa; Chyzh , Yulia (Problems of Cryobiology and Cryomedicine, 2020)
When studying the impact of nervous system on physiological and pathophysiological processes, a need arises to determine the contribution of each division of autonomic nervous system. For the nervus vagus ablation in cervical spine, chest and abdominal cavities the cryosurgical method has been designed to assess the effect of parasympathetic division on heart rate variability. There has been shown the possibility to implement the nervus vagus ablation, as well as the arteria carotis cryodenervation using cryosurgical technique in the ‘carotid’ triangle area of the neck, and thereby to ‘switch off’ the vascular intima-located baroreceptors from a regulatory link. The use of endoscopic device and cryosurgical technique for vascular denervation was established to enable the aortic arch baroreceptor ablation while preserving an anatomical integrity of the vessel. Since the isolation procedure for the nervus vagus abdominal branches in rat along the esophageal lateral edges is relatively accessible, it allows performing the cryodenervation of individual and both nerve branches along with esophagus. Probl Cryobiol Cryomed 2020; 30(1): 090–098